Important role of muscle carnosine in rowing performance - Baguet, Audrey; Bourgois, Jan; Vanhee, Lander; Achten, Eric; Derave, Wim (Journal of applied physiology (1985), 2010)
The role of the presence of carnosine (β-alanyl-L-histidine) in millimolar concentrations in human skeletal muscle is poorly understood. Chronic oral β-alanine supplementation is shown to elevate muscle carnosine content and improve anaerobic exercise performance during some laboratory tests, mainly in the untrained. It remains to be determined whether carnosine loading can improve single competition-like events in elite athletes. The aims of the present study were to investigate if performance is related to the muscle carnosine content and if β-alanine supplementation improves performance in highly trained rowers. Eighteen Belgian elite rowers were supplemented for 7 wk with either placebo or β-alanine (5 g/day). Before and following supplementation, muscle carnosine content in soleus and gastrocnemius medialis was measured by proton magnetic resonance spectroscopy ((1)H-MRS) and the performance was evaluated in a 2,000-m ergometer test. At baseline, there was a strong positive correlation between 100-, 500-, 2,000-, and 6,000-m speed and muscle carnosine content. After β-alanine supplementation, the carnosine content increased by 45.3% in soleus and 28.2% in gastrocnemius. Following supplementation, the β-alanine group was 4.3 s faster than the placebo group, whereas before supplementation they were 0.3 s slower (P = 0.07). Muscle carnosine elevation was positively correlated to 2,000-m performance enhancement (P = 0.042 and r = 0.498). It can be concluded that the positive correlation between baseline muscle carnosine levels and rowing performance and the positive correlation between changes in muscle carnosine and performance improvement suggest that muscle carnosine is a new determinant of rowing performance.